Government Bonds in Domestic and Foreign Currency : The Role of Institutional and Macroeconomic Factors - Claessens, Stijn (Wiley, 2013)
In contrast to some recent research, this paper finds that institutional and macroeconomic factors are related to the depth and currency composition of government bond markets. Using panel data for developed and emerging economies, we find several factors to be systematically associated with bond markets. Aside from economic size (already shown to affect the currency composition), this paper shows that investor bases matter. Economies with deeper domestic financial systems (measured by bank deposits and stock market capitalization) have larger domestic currency bond markets and issue less foreign currency debt, whereas foreign investor demand is positively related to the size and share of foreign currency bonds. Moreover, less flexible exchange rate regimes are associated with more foreign currency issuance. Other relevant variables include inflation, fiscal burden, legal origin, and capital account openness.